Coping Strategies for Depression, Stress, and Anxiety in Adolescent Living with HIV/AIDS: A Systematic Review - Nasywa Durrun; Alif Arfan Zamaludin; Olivia As-syifa (Public Health Study Program, Faculty of Health Science, State Islamic University (UIN) Syarif Hidayatullah Jakarta, Indonesia., 2026)
Adolescents with HIV/AIDS face elevated mental health risks from stigma, discrimination, and social pressure,yet effective strategies to strengthen their coping remain underdeveloped. This systematic review explored coping strategies used by HIV-positive adolescents to manage depression, stress, and anxiety, aiming to identify the most adaptive and effective approaches. A total of 360 articles were retrieved from PubMed and screened using Rayyan AI, followed by targeted keyword searches and manual selection based on inclusion criteria (English-language studies on coping with stress, depression, or anxiety among HIV-positive adolescents) and exclusion criteria (studies unrelated to HIV/AIDS, adolescents, or coping, and literature reviews). This yielded18 relevant studies from the USA, South Africa, Tanzania, Uganda, Kenya, Zambia, Botswana, and China, which underwent qualitative analysis. Finding shows that the most adaptive personal coping strategies include self-acceptance, positive thinking, emotional expression, physical activity, and spiritual practices such as prayer and self-reflection. Spiritual coping, especially prayer and faith-based reflection, emerged as a key component of emotion-focused coping, helping adolescents find meaning, reduce rumination, and achieve inner peace despite HIV-related stressors. Overall, adaptive personal coping strategies play a crucial role in alleviating depression, stress, and anxiety among this population. These findings highlight the importance of integrating psychosocial support—including spiritual and emotion-focused approaches—into responsive, evidence-based healthcare services for adolescents with HIV/AIDS. Policymakers and healthcare providers should prioritize such integration to better support the mental health and overall wellbeing of this vulnerable group. Keyword: Adolescents, Coping Strategies, HIV/AIDS, Mental Health